RECLAIMING MODERATE ISLAM IN NAHDLATUL ULAMA: Challenging the Dominant Religious Authority in Digital Platform (JOURNAL OF INDONESIAN ISLAM, 2022)
This article examines Nahdlatul Ulama’s attempts to face three challenges, its internal dynamic within the elite religious circle, the influence of its leadership at the grassroots level, and the rise of the new religious authorities who employ social media to enlarge their influence. Amidst the growth of internet users bridging the gap between rural and urban areas, this rise of new religious authority has steeply eroded NU's domination, which bases Islamic traditionalism in rural areas. This article contends that NU cannot be viewed as a singular face of religious orientation. However, in the level of ideology, NU’s aswaja (ahl as-sunnah wa al-jamā’ah) brings its followers into a moderate view. This religious orientation has been contested respectively amidst organizational structure and different geographical landscapes of NU's people. Meanwhile, the dominance of Islamic conservative groups in the digital platform appears to be quite strong. Because of these challenges, NU struggles to reclaim its religious authority at the level of the youngest circles.